Bordering the margins: perceptions of people with disabilities about professional dance (DAPesquisa, 2021)
This study’s proposal is to investigate how people with disabilities, dance students inserted in the context of non-formal education, perceive the field of artistic professional dance as a possibility for their bodies. This is a qualitative field research, using semi-structured interviews as a data collection instrument. The data were analyzed and discussed adopting the concept of Umwelt, proposed by Jacob von Uexkull, emphasizing the subjects’ own perceptions about the inclusion of their bodies, considered non-standard, in the artistic production of dance. The results indicated that the perception obout professional performance in dance is linked to the body and dance models of people without disabilities.
Keywords: Marginality, Social, in art; Dance for people with disabilities; Dancers with disabilities; Inclusive education